The polarization-dependent anisotropic Raman response of few-layer and bulk WTe2 under different excitation wavelengths. Issue 105 (1st November 2016) - Song, Qingjun; Wang, Haifeng; Xu, Xiaolong; Pan, Xingchen; Wang, Yilun; Song, Fengqi; Wan, Xiangang; Dai, Lun
Abstract : WTe2, which is an orthorhombic semimetal crystallized in Td phase, exhibts distinct in-plane anisotropy. The Raman modes depict different anisotropic response by rotating the incident polarization under different excitation wavelengths. Abstract : WTe2, an orthorhombic semimetal crystallized in Td phase, is a new transition metal dichalcogenide (TMD) that recently arouses great interest because of its properties of unsaturated giant magnetoresistance, Lifshitz transition and novel type II Weyl semimetal. Its covalently bonded W atoms form a zigzag W–W chain, which leads to the distinct in-plane anisotropy. In this paper, we investigate the polarization-dependent anisotropic Raman response of WTe2 with the thickness from monolayer to bulk under different excitation wavelengths, by rotating the incident laser polarization while fixing the sample and scattered polarization. The polar plots of the intensities for all detected modes exhibit two-lobed shape, while the main-axis orientations for different symmetric modes are different. These anisotropic results are first roughly fitted based on the Placzek approximated intensity, and then analyzed by the full quantum model considering the anisotropic electron–photon and anisotropic electron–phonon interactions. This work not only demonstrates the thickness and excitation wavelength dependence of the anisotropic Raman modes in WTe2, but also reveals the origin of the Raman anisotropy, which will be helpful for the research about anisotropic optical, electrical, and mechanical properties of TMDs as well as their device application.